New findings and challenges in OCT angiography for diabetic retinopathy - Sorour, Osama; Arya, Malvika; Waheed, Nadia (Annals of Eye Science; Vol 3 (August 2018): Annals of Eye Science, 2018)
Diabetic retinopathy (DR) is a leading cause of visual loss worldwide. Disease severity is graded from mild non-proliferative DR to proliferative DR. Optical coherence tomography angiography (OCTA) has become widely accepted as a useful noninvasive technique that provides detailed imaging of the ocular vessels. It is also becoming an increasingly essential tool for both qualitative and quantitative assessment of DR, especially with the advent of wider imaging capabilities. Various angiographic features of DR, such as microaneurysms, intraretinal microvascular abnormalities, neovascularization, and nonperfusion have been comprehensively studied and described using OCTA. Different quantitative OCTA metrics have been introduced, such as vessel density, foveal avascular zone (FAZ) area, and area of nonperfusion. Current research has been focusing on the application of quantitative OCTA for the diagnosis of DR and treatment monitoring. The primary purpose of this article is to review the use of OCTA, including its challenges, in the diagnosis and management of DR.